Report on the extension of Admiralty jurisdiction in Ireland to cases of freight and demurrage; prepared for the Council - Hutton, Henry Dix (Statistical and Social Inquiry Society of Ireland, 1870)
While the Court of Admiralty in Ireland has jurisdiction to proceed against the masters of ships at the suit of the merchants employing their vessels, it has no correlative power of entertaining complaints by captains in respect of freight or demurrage. This state of things causes delay, which involves hardship, and not unfrequently a practical denial of justice, since the Court of Admiralty sits all the year round, while the Superior Courts of Common Law only sit at intervals for the trial of such causes. The long vacation extends practically over four months, and during that period no cause can be brought to trial. Even in the other eight months the remedy is very slow, and may be so dilatory as to be practically useless. Such cases can only be tried at the sittings of each term, or at assizes (in March and July). The Consolidated Nisi Prius Court, which sits during term, has no jurisdiction in such cases; nor can the Courts of Quarter Sessions in Ireland deal with them beyond their ordinary jurisdiction of #40.
Read Tuesday, 14th June, 1870
Keywords: Admiralty court; Freight; 314.15